If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15 = 11 + -1x Reorder the terms: 15 + 3x = 11 + -1x Solving 15 + 3x = 11 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 15 + 3x + x = 11 + -1x + x Combine like terms: 3x + x = 4x 15 + 4x = 11 + -1x + x Combine like terms: -1x + x = 0 15 + 4x = 11 + 0 15 + 4x = 11 Add '-15' to each side of the equation. 15 + -15 + 4x = 11 + -15 Combine like terms: 15 + -15 = 0 0 + 4x = 11 + -15 4x = 11 + -15 Combine like terms: 11 + -15 = -4 4x = -4 Divide each side by '4'. x = -1 Simplifying x = -1
| 5x*(x-1)= | | 5x*(4x-5)= | | 3x+5=11-x | | Log(11-x)-log(2-x)=1 | | X^4-8x^3+18x^2-8x-1=0 | | 2xsquared-16=0 | | 9(x-6)=4x | | 25=(3x-2)(2x+5)(3x-2)2 | | 25=(3x-2)(2x+5)(3x-2) | | 8x-7w+5x+8y+5y+3w= | | 5x-3=x+7+3 | | 137+x=428 | | X^3+4x^3+4x=0 | | 5y-8=22-y | | 10x+5y+7z-5x+3z-9y= | | 11a-16=6a-1 | | 4y-14=18whatisy | | 8t+2=3t+12 | | 6.5=2x+3 | | 5+2x=5x-3(x-1)+2 | | x+(x-7)=67 | | 6x^3+x^2-35x=0 | | 5x-2=11x+5-6x | | 21x-4=18x+10 | | 66-3x=6-9 | | 6x-18=9x+6 | | 5x+4=(-1) | | (2sinx+1)(cosx-1)=0 | | 7p-2=p+12 | | 20a-16=12(3-a) | | z^2-(4+i)z+5+5i=0 | | 20a-16=12(3-a)thenais |